Development of Instructional Media on Mathematics Assisted Mobile Learning-Based with I-SPRING ON Algebraic Materials - Ririn Hanifah; Dwi Ivayana Sari; Nur Aini (Urogram Studi Pendidikan Matematika, Universitas IVET, 2022)
This study aims to develop mobile learning-based mathematics learning media that can be accessed offline, as a solution to the problems faced by students during the learning process from home. The test subjects of this study were 25 students of SMP Taman Sari. The research method uses the ADDIE development model which consists of 5 stages, namely: Analysis, Design, Development, Implementation, and Evaluation. From the research process carried out, the results obtained are media that are developed and practical to use. Keyword : Mathematics Learning Media, Applications, Mobile Learning.